Perancangan dan Implementasi E-Commerce Corrugated Carton Box Menggunakan Metode Rapid Application Development - Takasili, Tevin; Kristiyanti, Dinar Ajeng (Maranatha University Press, 2025)
PT Hora Cipta Jaya is a company specializing in the sale of corrugated cardboard boxes. PT Hora Cipta Jaya typically uses corrugated cardboard boxes to package goods or products for shipping. Due to their strength, durability, and recyclability, many industrial companies use them to package their products. PT Hora Cipta Jaya still conducts sales processes manually, starting from transactions, marketing, to recording and reporting. Employees still need to manually record all company data during sales using Excel. Errors often occur during the purchase and sale of products, such as mistakes in recording and pricing calculations, as well as errors in order data entry and shipping. The aim of this research is to assist the company in managing data and designing a system that features online ordering, payment, shipping, reporting, and product promotion. We developed this system using the RAD method, utilizing PHP programming language and MySQL database. The system development process is divided into four stages: requirements analysis, system design, system implementation, and application feasibility analysis. The research resulted in an e-commerce system that helps the company manage data, facilitates online product sales transactions and broader product marketing, and automatically records invoices and reports. All features of this system are now operational after successfully completing testing phases for both admin and customer parts using the black box testing method. The system scored 78 for the admin section and 79.5 for the customer section from each respondent using the System Usability Scale, achieving a class B rating (good category).